Nuclear pCHK1 as a potential biomarker of increased sensitivity to ATR inhibition. Issue 2 (8th December 2022) - Sundararajan, Vignesh; Tan, Tuan Zea; Lim, Diana; Peng, Yanfen; Wengner, Antje Margret; Ngoi, Natalie Yan Li; Jeyasekharan, Anand D; Tan, David Shao Peng
Abstract: Excessive genomic instability coupled with abnormalities in DNA repair pathways induces high levels of 'replication stress' when cancer cells propagate. Rather than hampering cancer cell proliferation, novel treatment strategies are turning their attention towards targeting cell cycle checkpoint kinases (such as ATR, CHK1, WEE1, and others) along the DNA damage response and replicative stress response pathways, thereby allowing unrepaired DNA damage to be carried forward towards mitotic catastrophe and apoptosis. The selective ATR kinase inhibitor elimusertib (BAY 1895344) has demonstrated preclinical and clinical monotherapy activity; however, reliable predictive biomarkers of treatment benefit are still lacking. In this study, using gene expression profiling of 24 cell lines from different cancer types and in a panel of ovarian cancer cell lines, we found that nuclear‐specific enrichment of checkpoint kinase 1 (CHK1) correlated with increased sensitivity to elimusertib. Using an advanced multispectral imaging system in subsequent cell line‐derived xenograft specimens, we showed a trend between nuclear phosphorylated CHK1 (pCHK1) staining and increased sensitivity to the ATR inhibitor elimusertib, indicating the potential value of pCHK1 expression as a predictive biomarker of ATR inhibitor sensitivity. © 2022 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.